The Role of Web Based Accounting Online System 2.0 as the Company's Income and Expense Management - Azizah, Nur; Supriyanti, Dedeh; Mustapha, Siti Fairuz Aminah; Yang, Holly (APTISI Transactions on Management (ATM), 2017)
In a company, the process of income and expense of money must have a profit-generating goal base. The success of financial management within the company, can be monitored from the ability of the financial management in managing the finances and utilize all the opportunities that exist with as much as possible with the aim to control the company's cash (cash flow) and the impact of generating profits in accordance with expectations. With a web-based online accounting system version 2.0, companies can be given the ease to manage money in and out of the company's cash. It has a user friendly system with navigation that makes it easy for the financial management to use it. Starting from the creation of a company's cash account used as a cash account and corporate bank account on the system, deletion or filing of cash accounts, up to the transfer invoice creation feature, receive and send money. Thus, this system is very effective and efficient in the management of income and corporate cash disbursements. Keywords:​Accounting Online System, Financial Management, Cash and Bank